If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y-y(.33)=167.50
We move all terms to the left:
y-y(.33)-(167.50)=0
We add all the numbers together, and all the variables
y-y(0.33)-(167.5)=0
We add all the numbers together, and all the variables
y-y(0.33)-167.5=0
We multiply parentheses
y-0.33y-167.5=0
We add all the numbers together, and all the variables
0.67y-167.5=0
We move all terms containing y to the left, all other terms to the right
0.67y=167.5
y=167.5/0.67
y=249+0.67/0.67
| 3.2a-24=4a | | 10=4+3(t+2 | | 9-150x+40=0 | | 30+17x=5x+2 | | x^/6+x/2+1/3=0 | | 4x^2+3-85=0 | | 3x-42=-7x+28 | | 21-15x-100x=0 | | -9+10k=51 | | -1/x^2=2,5x-5.25 | | -3+13=5x+21 | | 2x-1=-12x+15 | | 3/4(12x-8)=18 | | -2(7-2k)-4(k-7)=14 | | 2^x=65 | | 7x=2x-34 | | -3y+15=2y-20 | | 2x-10=-4x+8 | | Y=3x^2+15x+6 | | 7x-13=15x+11 | | 2(4x+30=-3(x-5) | | 7=9x-2 | | -129=-3(7-6p) | | 2x2+10x=48 | | -6+113x=-34 | | 6(x-4)=-13 | | 4=1/4x^2 | | 3x^2+(2x^2+x+1)(x+1)=12 | | 4x+6x=1x | | 9x-3-10=20 | | 6(x-4=-13 | | 3x+15=3(x-3) |